PREVALENCE AND SCREENING OF GESTATIONAL DIABETES MELLITUS IN PREGNANT WOMEN: A STUDY ON EARLY DETECTION AND MATERNAL-NEONATAL OUTCOMES - Dr. M L Pratyusha (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Gestational Diabetes Mellitus (GDM) is a common metabolic disorder during pregnancy that poses significant health risks to both the mother and the child. In this study, we aimed to evaluate the prevalence of GDM and the effectiveness of screening methods at different gestational stages. A total of 250 pregnant women were screened using the 50g Glucose Challenge Test (GCT) at 24-28 weeks and 32-34 weeks of gestation. The study found that 10 patients were diagnosed with GDM, and it was significantly associated with age above 30 years, especially over 35 years, as well as obesity and multigravidity. The analysis revealed that GDM had a higher prevalence in women with risk factors such as advanced maternal age and higher body weight. The study also highlighted that infants born to GDM mothers were more likely to have complications such as cardiac anomalies, prematurity, hypoglycemia, and hyperbilirubinemia. The findings underscore the importance of universal screening for GDM to prevent adverse maternal and neonatal outcomes and emphasize the need for early diagnosis and intervention to manage GDM effectively.